Development and Evaluation of a Novel-Thymol@Natural-Zeolite/Low-Density-Polyethylene Active Packaging Film: Applications for Pork Fillets Preservation - Constantinos E. Salmas; Aris E. Giannakas; Vassilios K. Karabagias; Dimitrios Moschovas; Ioannis K. Karabagias; Christina Gioti; Stavros Georgopoulos; Areti Leontiou; George Kehayias; Apostolos Avgeropoulos; Charalampos Proestos (MDPI AG, 2023)
Sustainability, the circular economy, and the "greenhouse" effect have led the food packaging industry to use naturally available bio-compounds. The integration of such compounds in packaging films increases food safety and extends food shelf-life. The development of an active/antioxidant packaging film based on the widely commercially used low-density polyethylene, natural zeolite, and Thymol, a natural extract from thyme oil, is presented in this work. The obtained active films were characterized using X-Ray Diffraction, Fourier-Transform Infrared Spectroscopy, Scanning Electron Microscopy, and Differential Scanning Calorimetry techniques. The tensile strength, water-oxygen barrier properties, and total antioxidant activity were measured. Low-density polyethylene incorporated with Thymol@Natural Zeolite at a proportion of 15 wt% was the most promising material and was used as film to wrap-up pork fillets. The thiobarbituric acid (TBA) method and heme iron measurements indicated a delayed lipids oxidation using this film. A linear correlation between the TBA method and heme iron values seems to be established, which could result in a fast method to determine the degree of lipid oxidation in pork fillets. Finally, a two-stage diffusion process during Thymol release was observed, and the values of the diffusion coefficient was 2.09 × 10−7 and 1.21 × 10−8 cm2/s for each stage. The applied pseudo-second sorption model provided a rate constant k2 = 0.01647 (s−1). These results indicate the strong potential of such films to be used as food packaging materials free of E-number preservatives.